2010
DOI: 10.1183/09031936.00122209
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hay and animal feed exposure on respiratory status: a longitudinal study

Abstract: Our aim was to study respiratory symptoms and lung function decline in farmers, with particular attention to the influence of handling hay, straw and animal feed.From a cohort recruited in 1993-1994, 219 (82.6%) dairy farmers, 130 (62.5%) nondairy agricultural workers and 99 (66.4%) controls were re-evaluated in 2006. They answered medical and occupational questionnaires, underwent spirometric tests at both evaluations and pulse oximetry in 2006.Dairy and nondairy agricultural workers showed an increased risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
(48 reference statements)
3
35
1
1
Order By: Relevance
“…GOLD criteria II+ was the most prevalent (92)(93)(94)(95). The FEV 1 and FEV 1 /FVC were the outcome in two studies (91,97), like FEV 1 /FVC<0.7 and <LLN (96,98). All eight studies found an association between airway obstruction/COPD and occupational exposure.…”
Section: Publications Since the Initial Reviewmentioning
confidence: 93%
See 3 more Smart Citations
“…GOLD criteria II+ was the most prevalent (92)(93)(94)(95). The FEV 1 and FEV 1 /FVC were the outcome in two studies (91,97), like FEV 1 /FVC<0.7 and <LLN (96,98). All eight studies found an association between airway obstruction/COPD and occupational exposure.…”
Section: Publications Since the Initial Reviewmentioning
confidence: 93%
“…Five of these (91)(92)(93)(94)(95) were cross-sectional and three (96)(97)(98) were longitudinal with a follow-up time between 5-13 years. Six studies came from Europe (91,92,94,(96)(97)(98) and one study each from the US (93) and South Africa (95).…”
Section: Publications Since the Initial Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, all of these populations are exposed to wheat dust. Moreover, work-related respiratory effects have been proved, even after the 2000s, in terminal elevator operators [4], livestock and dairy farmers [2,5,9,10,11,12], and grain farmers [13], by epidemiological studies conducted on these populations. However, no data are available on populations of harvesters and straw ball makers, mainly because they are only seasonally exposed to wheat.…”
Section: Introductionmentioning
confidence: 99%